Sustainable Learning for Students with Intellectual Disability: A Cross-Curricular Approach to Adaptive Skill Development - Kayla Canis; Kaylee Smith; Caitlyn Ryan; Miriam Boesch (Educational Considerations, 2025)
Adaptive skills are crucial for students with intellectual disability (ID) particularly in preparing for post-secondary transition and long-term independence as it allows them to take care of themselves, communicate effectively, and participate fully across settings. Special education teachers and related service personnel play a major role in helping students with ID build adaptive skills. As such, the focus of this paper is to highlight how sustainable adaptive skill development can be strengthened through Individualized Education Program (IEP) goals and instructional practices. Specifically, the paper outlines: (a) the value of integrating adaptive skills within academic instruction through cross-curricular activities that foster meaningful, real-world connections, (b) practical strategies to help design instruction that aligns with students’ individualized needs while reinforcing functional outcomes, and (c) the role of educator training and professional learning in supporting the successful implementation of adaptive skill instruction. The intent is to raise awareness, offer actionable strategies, and promote thoughtful IEP development that supports students in leading successful, independent lives.
Keywords: Curriculum design; Instructional strategies; Intellectual disability; Life skills instructional strategies; Transition planning